Inoculation of Endophytic Bacteria for Increasing Plant Height and Number of Rice Roots (Oryza sativa) - Fari Fadilah; Triastuti Rahayu; Putri Agustina; Kistantia Elok Mumpuni; Listy Hasti Mandiri; Trio Ageng Prayitno; Yasir Sidiq (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Four endophytic bacteria have been isolated from banana kluthuk plants and banana ambon. Previous study showed that they produce Indole Acetic Acid (IAA). This study aimed to analyze the effect of endophytic bacterial inoculation on plant height and the number of rice root. For this reason, two endophytic bacteria of each klutuk banana and ambon banana plants were cultured and examined for growth rate using a 600 nm spectrophotometer. Isolate growth was calculated every two hours for 16 hours of bacterial growth in NB media. Bacterial inoculation experiments on rice plants were carried out with five replications. This inoculation begun with germination of rice seeds until the radicle was observed. Then germinated rice seedlings were soaked in a bacterial suspension for 1 hour at room temperature. The results showed the exponential phase of all isolates was observed at 6 hours with shaking. Inoculation using A22 and A51 isolates significantly increases plant height, number of leaves. While, A22 isolate significantly increased the number of roots compared to the uninoculated plants (control). It supports the potential of endophytic bacteria from banana kluthuk and ambon plants.